2016
DOI: 10.1155/2016/4186086
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Interstitial Nephritis Presenting as Hypercalcemia and Nephrolithiasis

Abstract: We report a case of acute kidney injury as the initial manifestation of sarcoidosis. A 55-year-old male was sent from his primary care physician's office with incidental lab findings significant for hypercalcemia and acute kidney injury with past medical history significant for nephrolithiasis. Initial treatment with intravenous hydration did not improve his condition. The renal biopsy subsequently revealed granulomatous interstitial nephritis (GIN). Treatment with the appropriate dose of glucocorticoids impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Renal failure or renal disorder is may also cause by granulomatous interstitial nephritis (GIN) [16], a rare condition. Sarcoidosis, granulomatous with polyangiitis, and infectious agents are the most common causes (particularly renal tuberculosis).…”
Section: Kidneymentioning
confidence: 99%
“…Renal failure or renal disorder is may also cause by granulomatous interstitial nephritis (GIN) [16], a rare condition. Sarcoidosis, granulomatous with polyangiitis, and infectious agents are the most common causes (particularly renal tuberculosis).…”
Section: Kidneymentioning
confidence: 99%
“…4 Furthermore, sarcoidosis may relapse isolated in the kidney after treatment of initial presentation with multiple organ involvement. 24 However, careful review of reported cases of isolated renal sarcoidosis reveals a history of drug intake associated with GIN, such as non-steroidal anti-inflammatory drug (NSAID), 25 or extrarenal disease manifestations, such as mediastinal and hilar lymphadenopathy 26 or joint involvement, 27 in some. In these cases, the diagnosis of isolated renal sarcoidosis may be doubted.…”
Section: Differential Diagnosis Of Isolated Renal Sarcoidosismentioning
confidence: 99%
“…Disturbance in calcium balance occurs due to extrarenal excess production of 1,25-dihydroxyvitamin D by sarcoid macrophages and, subsequently, increased intestinal absorption of calcium. [12][13][14] Biopsy will reveal infiltration of mononuclear cells to the interstitium leading to formation of non-caseating granulomas and chronic interstitial fibrosis. [4,5,15] Although uncommon, renal involvement in childhood sarcoidosis is usually diagnosed relatively late and 40% of affected children will continue with insufficiency after treat-ment.…”
Section: Introductionmentioning
confidence: 99%